Knowledge, attitudes, and practices towards seasonal influenza vaccination among pregnant women and healthcare workers: A cross‐sectional survey in Afghanistan. Issue 3 (21st March 2023) - Shahid, Shahira; Kalhoro, Shafi; Khwaja, Hajra; Hussainyar, Mohammad Asif; Mehmood, Junaid; Qazi, Muhammad Farrukh; Abubakar, Abdinasir; Mohamed, Shaza; Khan, Wasiq; Jehan, Fyezah; Nisar, Muhammad Imran
Abstract: Background: Despite recommendation by the World Health Organization (WHO), influenza vaccination coverage among high‐risk groups remains suboptimal in Afghanistan. This study aims to document the knowledge, attitudes, and practices of seasonal influenza vaccine uptake among two priority groups, pregnant women (PWs) and healthcare workers (HCWs). Methods: This cross‐sectional study enrolled PWs and HCWs in Kabul, Afghanistan, from September to December 2021. Data on vaccine intention and uptake, knowledge, and attitudes towards vaccination were collected. Simple linear regression was used to predict the impact of sociodemographic characteristics on the KAP score. Results: A total of 420 PWs were enrolled in Afghanistan. The majority (89%) of these women had never heard of the influenza vaccine but 76% intended to receive the vaccine. Of the 220 HCWs enrolled, 88% were unvaccinated. Accessibility and cost were factors which encouraged vaccination among HCWs. Fear of side effects and affordability were identified as key barriers. HCWs reported high level of vaccine intention (93%). PWs aged under 18 years ( β : 6.5, P = 0.004), between 18 and 24 years ( β : 2.9, P = 0.014), currently employed ( β : 5.8, P = 0.004), and vaccinated against COVID‐19 ( β : 2.8, P = 0.01) were likely to have a higher attitude score. Among HCWs, being female was a predictor for poor vaccination practice ( β : −1.33, P < 0.001) whereas being vaccinated against COVID‐19 was a predictor for higher practice score ( β : 2.4, P < 0.001). Conclusion: To increase influenza vaccination coverage among priority groups, efforts should be made to address issues such as lack of knowledge, limited availability, and cost barriers.